Comment on `Performance analysis in football: A critical review and implications for future research` - Carling, C.; Wright, C.; Nelson, L. J.; Bradley, P. S. (Journal of Sports Sciences, 2014)
MacKenzie and Cushion (2013) recently reviewed performance analysis research in association football (soccer). Their critical review focused on several themes related to methodological approaches such as sample size, match context and operational definitions and the implications of research findings to professional practice. In this response letter, the authors comment on additional pragmatic concerns regarding these key themes as well as some of the difficulties commonly faced when conducting performance analysis research.